Aerodynamic hysteresis of a discus - Seo, K.; Ohta, K.; Ohgi, Y.; Kimura, Y. (Procedia Engineering, 2013)
This paper describes the hysteresis in the aerodynamic properties of a discus near to its stalling angle. Wind tunnel tests were carried out with a full-size woman's discus. The experimental aerodynamic data D, L and M were obtained from wind tunnel tests as functions of the angle of attack and the spin rate. It was found that the drag, lift and pitching moment coefficients, CD CL and CM, increase with increasing the angle of attack up to a stalling angle of 28-30°. Beyond the stalling angle, CL and CM decrease suddenly and abruptly with increasing angle of attack. On the other hand, recovery from the stall does not occur at the same stalling angle of 28-30° when the angle of attack decreases from the stall state; recovery actually occurs at 25°. The CL -a (angle of attack) curve is almost the same when the angle of attack is less than 24°. Therefore, hysteresis occurs near the stalling angle.